Pyropia yezoensis genome reveals diverse mechanisms of carbon acquisition in the intertidal environment - Wang, Dongmei (Nat Commun, 2020)
Changes in atmospheric CO(2) concentration have played a central role in algal and plant adaptation and evolution. The commercially important red algal genus, Pyropia (Bangiales) appears to have responded to inorganic carbon (C(i)) availability by evolving alternating heteromorphic generations that occupy distinct habitats. The leafy gametophyte inhabits the intertidal zone that undergoes frequent emersion, whereas the sporophyte conchocelis bores into mollusk shells. Here, we analyze a high-quality genome assembly of Pyropia yezoensis to elucidate the interplay between C(i) availability and life cycle evolution. We find horizontal gene transfers from bacteria and expansion of gene families (e.g. carbonic anhydrase, anti-oxidative related genes), many of which show gametophyte-specific expression or significant up-regulation in gametophyte in response to dehydration. In conchocelis, the release of HCO(3)(-) from shell promoted by carbonic anhydrase provides a source of C(i). This hypothesis is supported by the incorporation of (13)C isotope by conchocelis when co-cultured with (13)C-labeled CaCO(3).